SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DENGAN METODE RAD (RAPID APPLICATION DEVELOPMENT) (STUDY KASUS SMK MUHAMMADIYAH KAWALI) - Faisal Zabani, Muhamad; Yudi Permana, Nana; Mulyana, Dadan (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
The purpose of this research is to design a web-based library information system to make it easier for librarians to manage data and for library users to find book collections. Previously, the library still used separate Microsoft Excel spreadsheets for all administration. This non- integrated system leads to inefficient services, such as slow information retrieval, the risk of data errors, and difficulty for library users in finding book availability. To solve this problem, the author used the Rapid Application Development (RAD) method to build a web-based application with PHP and MySQL. The result is an integrated library website that makes administrative management more efficient and accurate.